2007
DOI: 10.1123/jpah.4.2.167
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Park Proximity and Social Support in Shaping Park Visitation, Physical Activity, and Perceived Health Among Older Adults

Abstract: Background:Health scholars purport that park proximity and social support promotes physical activity and health. However, few studies examine the combined contributions of these constructs in shaping physical activity and health.Purpose:In this study, the contributions of environmental and social characteristics in shaping park use, physical activity, and health are examined.Methods:A survey was distributed to 1515 older adults in Cleveland, Ohio. Results: Path analysis indicated that social support was direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 10 publications
6
107
0
1
Order By: Relevance
“…Given that demographics and past park use have been shown to influence perceptions of parks [33,64,65] as well as physical activity and health [29,[66][67][68][69][70], gender, age, income, race/ethnicity, and past park use were controlled for in the four models. To categorize past park use, respondents who indicated that they had not visited a park within the last month were treated as nonvisitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that demographics and past park use have been shown to influence perceptions of parks [33,64,65] as well as physical activity and health [29,[66][67][68][69][70], gender, age, income, race/ethnicity, and past park use were controlled for in the four models. To categorize past park use, respondents who indicated that they had not visited a park within the last month were treated as nonvisitors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies show differences between perceived versus objective measures of park characteristics [25][26][27], and perceived measures may be even more important in predicting physical activity and health [28,29]. Specifically, although studies indicate that people may not always know accurate information about their parks [27,30], these perceptions, even if incorrect compared with observational measures, are significant because people make their decisions based on their perceptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El apoyo social se manifiesta física y psicológicamente en la salud. El apoyo emocional es el que más fuertemente se ha relacionado con la salud, aunque el apoyo material también contribuye, pero en menor grado (Glover y Parry, 2008;Mowen, Orsega-Smith, Payne, Ainsworth y Godbey, 2007;Sasidharan et al, 2006).…”
Section: Recreación Amistad Y Apoyo Socialunclassified
“…Moreover, while accessibility has now evolved into a multidimensional construct, current open-space planning models still use physical proximity to parks as a proxy variable to evaluate 'accessibility' (Babey et al, 2013;Andrew T Kaczynski et al, 2014;A. Mowen, Orsega-Smith, Payne, Ainsworth, & Godbey, 2007;Neuvonen, Slevanen, Tonnes, & Koskela, 2007).…”
Section: Introductionmentioning
confidence: 99%